2008
DOI: 10.1097/01.nna.0000312758.14536.e0
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Nurse Managers Stay? Building a Model of Engagement

Abstract: The short tenure of nurse managers is an urgent aspect of the leadership vacuum within the nursing shortage. The authors, who sought to build a model of nurse manager engagement in contrast to a retention model, continue to report data from a national qualitative study funded by The Robert Wood Johnson Foundation of 30 outstanding and longtime nurse managers in 6 settings. Part 1 (March 2008) described the dimensions and applications of individual engagement. In this article (part 2), the authors describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 16 publications
2
60
0
Order By: Relevance
“…Effective leadership preparation and commitment of the nurse manager can lead to enhanced staff nurse retention, reduced turnover costs, and improved quality and financial outcomes for healthcare institutions. 24 This program offered evidence-based leadership content within a contemporary context to nurse managers and provided an opportunity for nurse executives to use a common language to share their values, expectations, and expertise on key organizational objectives influenced by nurse managers. The conceptual framework of the program leveraged the strength of the evidence and system-level support.…”
Section: Resultsmentioning
confidence: 99%
“…Effective leadership preparation and commitment of the nurse manager can lead to enhanced staff nurse retention, reduced turnover costs, and improved quality and financial outcomes for healthcare institutions. 24 This program offered evidence-based leadership content within a contemporary context to nurse managers and provided an opportunity for nurse executives to use a common language to share their values, expectations, and expertise on key organizational objectives influenced by nurse managers. The conceptual framework of the program leveraged the strength of the evidence and system-level support.…”
Section: Resultsmentioning
confidence: 99%
“…Antecedents to transformation behaviors and outcomes. [3][4][5]10,11,13,18,20,22,25,26 Digital Content 1, http://links.lww.com/JONA/A264) was developed to identify the categories of work and activities and the frequency by which they were performed. Institutional review board (IRB) approval was obtained through Rutgers University in addition to IRB approval at the study sites.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] Evidence demonstrates that independent of knowledge and skill, there are organizational and work design factors that promote or impede transformational behaviors among leaders. 3,4,11 As the healthcare environment is redesigned to meet the challenges of access, quality, and value, FLNMs are pivotal in helping to change the environments of acute care hospitals. The Institute of Medicine report, The Future of Nursing Leading Change, Advancing Health, identified that ''strong leadership is critical if the vision of a transformed healthcare system is to be realized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies included encouraging use of vacation time and offering vouchers for massages, take-out dinners, and health club memberships. 1 Unfortunately, these strategies do not seem sustainable.…”
mentioning
confidence: 99%